2011
DOI: 10.1002/art.30280
|View full text |Cite
|
Sign up to set email alerts
|

A novel N‐ethyl‐N‐nitrosourea–induced mutation in phospholipase Cγ2 causes inflammatory arthritis, metabolic defects, and male infertility in vitro in a murine model

Abstract: Objective. It is difficult to identify a single causative factor for inflammatory arthritis because of the multifactorial nature of the disease. This study was undertaken to dissect the molecular complexity of systemic inflammatory disease, utilizing a combined approach of mutagenesis and systematic phenotype screening in a murine model.Methods. In a large-scale N-ethyl-N-nitrosourea mutagenesis project, the Ali14 mutant mouse strain was established because of dominant inheritance of spontaneous swelling and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
138
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(139 citation statements)
references
References 43 publications
1
138
0
Order By: Relevance
“…In addition we showed that under normal growth conditions there is no evidence for lower cGMP concentrations in daf-11 mutants than in wild-type animals proposing that not only low cGMP levels are responsible for the extended lifespan of daf-11 mutants [1].…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…In addition we showed that under normal growth conditions there is no evidence for lower cGMP concentrations in daf-11 mutants than in wild-type animals proposing that not only low cGMP levels are responsible for the extended lifespan of daf-11 mutants [1].…”
mentioning
confidence: 71%
“…Daf-11 is one of the receptor-bound GCs in C. elegans and an ortholog of human particulate guanylyl cyclase A (pGC-A). pGC-A has not been shown yet to be in involved in mammalian oxidative stress response, but previous studies in C. elegans showed that daf-11 loss of function mutants have a significant higher life expectancy under normal and oxidative stress conditions than wild-type nematodes due to lower cGMP concentrations [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations